Physical training in blood pressure and metabolic disturbances correction in young patients with Stage I arterial hypertension - N. P. Lyamina; A. V. Shevchenko; V. N. Senchikhin (Кардиоваскулярная терапия и профилактика)
Aim. To study effects of long-term, moderate-intensity controlled physical training (CPT) on blood pressure (BP) level and metabolic disturbances (MD) in young men with Stage I arterial hypertension (AH). Material and methods. The study included 49 men aged 18-45 years, with I Stage AH and MD, adhering to nonpharmaceutical lifestyle modification recommendations. Twenty-three patients additionally underwent long-term, moderate-intensity CPT for at least 6 months. Every 3 months, 24-hour BP monitoring, Doppler echocardiography (EchoCG), treadmill test, anthropometry with body mass index (BMI) calculation, lipid and carbohydrate profile assessment were performed. Results. Systematic moderate-intensity CPT course lasting for at least 3 months promoted decrease in systolic and diastolic BP (SBP, DBP). Long-term (6 months or longer) moderate-intensity CPT significantly reduced SBP and DBP levels, normalized SBP and DBP variability, restored circadian BP profile, beneficially influenced lipid and carbohydrate metabolism. Conclusion. Long-term, systematic moderate-intensity CPT in young men with Stage I AH demonstrated antihypertensive, anti-atherogenic, and metabolically neutral effects.